Indicadores microbianos e resposta à alteração da temperatura e adição de nutrientes em solos do bioma Cerrado - Oliveira, Suelen Martins de (2019)
The conversions of natural ecosystems in agrosystems and global climate changes have altered the functioning of soils with reflexes in microbial indicators of soil quality. In this sense, the objectives of this work were: (1) to determine microbial indicators of soil quality in different textural classes and phytophysiognomies; (2) to evaluate the impact of temperature increase and soil microbial respiration sensitivity at temperature (Q10) the addition of nitrogen in the soils and (3) to evaluate the impact of the addition of carbon (C), nitrogen (N) and phosphorus (P) in the soil microbial respiration (SMR). For this, soil samples were collected in nine natural ecosystems, here called sites (S1 to S9), belonging to the Cerrado biome, in the state of Minas Gerais. The soil samples were characterized physically and chemically and some of them were used for the determination of general and specific indicators and assembly of tests. In one of these tests, the treatments corresponded to the combination of nine sites, two doses of N (0 and 100 mg N kg soil-1) and three evaluation temperatures (20, 25 and 30ºC). On the other, soil samples were incubated with addition of the following treatments: C, N, P, CN, CP, NP, CNP and control (CT). The data were submitted to univariate, multivariate and Pearson correlation analyzes. The soils of very clayey texture (S1, S2 and S3) showed higher activity of soil quality microbial indicators than the loamy sand texture site (S9). In general, in very clayey soils the phytophysiognomy Forest (S2) presented greater activity of these indicators in relation to the Cerrado sensu stricto (S3); already in the sand clay textural class, the sites with phytophysionognomy of Forest type (S4, S5 and S6) presented higher activity of the indicators than the Cerradão (S7). Although the soil with higher clay content (S1, S2, S3, S4, S5 and S6) showed higher SMR values than less clayey soils (S7, S8 and S9), under higher temperature, the value of Q10 was higher in these last sites. The effect of the addition of N in Q10 can not be generalized and each ecosystem should be evaluated particularly. The results indicated that the SMR response to most sites was limited by the availability of C and the intensity of this effect was regulated by the preexisting nutrient availability in the soil at each site. Most of the sites showed higher SMR when C and P were added together. In the perspective of changes in the microbial functioning of soils caused by land use change and global environmental changes, it is expected that the results obtained in this work will be used as reference in future research to evaluate microbial indicators of soil quality and related processes in regions of the Cerrado biome.